A DNA Methylation-Based Panel for the Prognosis and Diagnosis of Patients With Breast Cancer and Its Mechanisms - Liu, Xiao-Ping; Hou, Jinxuan; Chen, Chen; Guan, Li; Hu, Han-Kun; Li, Sheng (Frontiers in Molecular Biosciences, 2020)
Objective To identify DNA methylation related biomarkers in patients with breast cancer (BC). Materials and methods A total of 7 BC methylation studies including 1,438 BC patients or breast tissues were included in this study. An elastic net regularized Cox proportional hazards regression (CPH) model was used to build a multi CpG methylation panel. The diagnosis and prognosis power of the panel was evaluated and validated using Kaplan-Meier curve, univariate and multivariable CPH, subgroup analysis. A nomogram containing the panel was developed. The relationships between the panel-based methylation risk and the immune landscape and genomic metrics were investigated. Results 68 CpG sites were significantly correlated with the overall survival (OS) of BC patients, and based on the result of penalized CPH, a 28-CpG site based multi CpG methylation panel was found, the prognosis and diagnosis role of the panel was validated in the discovery set, validation set, and 6 independent cohorts, which indicated that higher methylation risk was associated with poor OS, and the panel outperformed currently available biomarkers and remained an independent factor after adjusting for other clinical features. The methylation risk was negatively correlated with innated and adaptive immune cells, and positively correlated with total mutation load, SCNA and MATH. Conclusions We validated a multi CpG methylation panel that could independently predict the OS of BC patients. Th2-mediated tumor promotion effect, suppression of innate and adaptive immunity participated in the progression of high-risk BC. Patients with high methylation risk were associated with tumor heterogeneity and poor survival.